Natural Reforestation in the Felling Sites in the North Taiga Lowland Area of Western Siberia - Konstantin A. Bashegurov; Andrey N. Gavrilenko; Ekaterina P. Rozinkina; Artem S. Popov; Sergey V. Zalesov; Irina V. Predeina (Lesnoy Zhurnal (Forestry Journal), 2025)
The indicators of undergrowth accumulation in the felling sites of the West Siberian north taiga lowland forest area have been analyzed. The undergrowth has been recorded on the plots measuring 2×2 m in the amount of 30 plots on each studied felling site. It is noted that reforestation in the study area is proceeding quite successfully. In the conditions of green moss-berry and wild rosemary-lingonberry forest types, the undergrowth includes Scots pine (Pinus sylvestris L.), silver (Betula pendula Roth.) and downy (B. рubescens Ehrh.) birch, Siberian stone pine (Pinus sibirica Rupr.), aspen (Populus tremula L.), Siberian spruce (Picea obovata Ledeb.) and Siberian larch (Larix sibirica Ledeb.) with the dominance of Scots pine and silver birch. The high proportion of birch is explained by the annual seed production of the species and the transfer of seeds by wind over long distances, as well as its ability to vegetatively renew. The regeneration of coniferous species is inhibited by the periodicity of seed years, the suspension of seeds in the forest litter and moss thalli. These problems can be solved by soil mineralization. It is better to combine mineralization with the clearing of felling sites from felling residues. The latter are bulldozed onto a skidding trail from 2 sides. As a result of mixing the felling residues with the forest litter and soil, wood destruction processes are activated and the fire hazard at the felling site is minimized, and ideal conditions for the accumulation of undergrowth are created. The main area between the skidding trails (65–70 %) remains without mineralization, since in this part of the felling site, the maximum amount of pre-generation undergrowth is preserved during logging operations. In the conditions of the northern taiga subzone of the Khanty-Mansy Autonomous Okrug – Yugra, where the average wood increment is 0.6 m3/ha, the raw material value of the stands gives way to the ecological value. Considering the important ecological role of silver and downy birch, it is ...